Being you : The body image book for boys - Markey, Charlotte N.; Hart, Daniel; Zacher, Douglas N. (Cambridge University Press, 2022)
"From early childhood boys often feel pressured to be athletic and muscular. But what impact does this have on physical and mental well-being through their teens and beyond? Worryingly, a third of teen boys are trying to 'bulk up' due to body dissatisfaction, and boys and men account for 25% of eating disorder cases. What can we tell our boys to help them feel happy and confident simply being themselves? Being You has the answers! It's an easy-to-read, evidence-based guide to developing a positive body image for boys aged 12+. It covers all the facts on puberty, diet, exercise, self-care, mental health, social media, and everything in-between. Boys will find answers to the questions most on their mind, the truth behind many diet and exercise myths, and real-life stories from other boys. Armed with this book, they will understand that muscles don't make a man - it's enough simply being you!!"--